2014
DOI: 10.5861/ijrsm.2014.775
|View full text |Cite
|
Sign up to set email alerts
|

Impulse buying behavior of Vietnamese consumers in supermarket setting

Abstract: The goal of this paper is to identify factors affecting consumer impulse buying behaviors at supermarkets in Vietnam. Impulse purchase or impulse buying portrays purchases that shopper makes without any intention planned before shopping trip. This study attempts to analyze the impact of various variables extracted from internal, external, demographics, social perspectives on consumer impulse buying behavior. Quantitative questionnaire is used to measure responses of participants. The statistical analysis metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 40 publications
3
30
1
Order By: Relevance
“…Lastly, they can be defined as more active in their shopping behavior since they frequently engage in impulse purchasing than people who are demonstrate less impulsive behavior. Cho et al (2014) states that it is paramount for marketers to understand the unplanned buying behavior in order to devise marketing strategies and drive tactics from these strategies. Kollat and Willet (1967) state that consumers' demographics has an impact on impulsive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, they can be defined as more active in their shopping behavior since they frequently engage in impulse purchasing than people who are demonstrate less impulsive behavior. Cho et al (2014) states that it is paramount for marketers to understand the unplanned buying behavior in order to devise marketing strategies and drive tactics from these strategies. Kollat and Willet (1967) state that consumers' demographics has an impact on impulsive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that more knowledge on how the various external factors when applied may assist business to utilise their resources in a more efficient and effective manner. There are numerous external factors explored in literature [20]- [27], however, this study focuses on in-store browsing, store layout, sales personnel, store-atmosphere, promotional events and reference groups.…”
Section: Determinants Of Impulsive Purchasing Behaviourmentioning
confidence: 99%
“…In-store Browsing: In-store browsing is a component of impulsive purchasing process refers to consumers scanning items in shops for the purpose of obtaining information about products/services without any plan to buy or for the sake of curiosity. Researchers believe that it is in-store browsing that consumers are exposed to stimuli which creates the urge to purchase on impulse particularly when consumers spend more time browsing [20] [21] [22] believed that consumers who perform in-store browsing make unplanned buying because it is at this stage a consumer encounters desired products. Cho et al [20] analysed the driving factors behind impulsive purchasing behaviour of consumers in Vietnam supermarkets and found that in-store browsing plays a vital role in setting off impulsive purchasing activity.…”
Section: Determinants Of Impulsive Purchasing Behaviourmentioning
confidence: 99%
See 2 more Smart Citations